(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article presents the results of pedagogical experiments to study the influence of value motives for physical exercise on the health status of students in the process of physical education. Based on this, it becomes possible to determine the lagging link (physical quality) and identify the main training strategy characteristic of this group of students, because One of the tasks of physical education of students is the diversified development of physical qualities.